Antitumor effects of zerumbone on rat hepatocarcinoma and HEPG2 cells - Taha, Manal Mohamed Elhassan (2011)
Zerumbone (ZER), a monosesquiterpene found in the subtropical ginger tZingiber zerumbet Smith), possesses antiproliferative properties to several cancer cell lines, including cervical, skin and colon cancers. In this study, the antitumor effects of ZER were assessed in rats induced to develop liver cancer with a single intraperitoneal injection of diethylnitrosamine (DEN, 200 mg/kg body wt.) followed two weeks later by daily dietary 2-acetylaminofluorene (AAF, 0.02%) for another two weeks. Eighty rats were divided into 16 equal groups (n=5), comprising of normal (control) rats at three sacrifice times (3 groups), rats with induced hepatocarcinogenesis at three sacrifice times [positive control (DEN/ AAF)] (3 groups), rats with induced hepatocarcinogenesis given three ZER treatment doses (15, 30 or 60 mg/kg body wt.) each at three sacrifice times (9 groups) and normal rats treated with ZER (60 mg/kg body wt.) and sacrificed at end of experiment (1 group). Treated rats received intraperitoneal ZER injections twice weekly for 4, 8 or 11 weeks after AAF treatment. The effects of ZER on rat hepatocarcinogenesis were studied through body weight profile, apoptosis proteins (Bax and Bcl-Z), (1- fetoprotein (AfP), glutathione (GSH), glutathione S-transferase (GST), glutathione peroxidase (GPx), aspartate aminotransferase (AST), alanine transaminase (ALT), alkaline phosphatase (AP) and y-glutamyltranspeptidase (yGT) concentrations, TUNEL and lipid peroxidation assays, histopathological examinations, immunohistochemical staining of cell proliferation marker (peNA), transmission electron microscopy and AFP and apoptosis genes expressions using realtime quantitative polymerase chain reaction. The current study also used the liver cancer cell line (J-IepG2) as the in vitro model. The effects of ZER on liver cancer cells were determined by the MTT, caspase-3 and reactive oxygen species assays, inverted light microscopy, Hoechst DNA stain, and estimation of lactate dehydrogenase (LDH), AST, ALT and yGT concentrations in HepG2 cell culture media. The in vivo study showed that, the hepatocytes of positive control (DEN/AAF) rats were smaller with larger hyperchromatic nuclei than normal, showing cytoplasmic granulation and intracytoplasmic violaceous material, which were characteristic of hepatocarcinogenesis. Histopathological evaluations showed that ZER protects the rat liver from the carcinogenic effects of DEN and AAF. Liver weights and body weights were not statistically (P>O.05) different among groups. Rats in DEN/AAF group showed the relative liver weights. Serum ALT, AST, AP and AFP concentrations were significantly lower (P<O.05) in ZER-treated than untreated rats with liver cancer. The liver malondialdehyde (MDA) concentrations significantly (P<O.05) increased in the untreated DEN/AAF rats indicating hepatic lipid peroxidation. There was also significant (p<O.05) reduction in the hepatic tissue GSH concentrations III these rats. The liver sections of untreated DEN/ AAF rats also showed abundant PCNA, while in ZER-trcated rats the expression of this antigen was significantly (P<O.05) lowered. Formalin-fixed paraffin-embedded liver sections of untreated DEN/AAF rats also showed abundant AFP immunocxpression, while in ZER-treated rats the expression of this protein was significantly (P<O.05) lowered. The realtime qPCR analysis also showed significantly (P<O.05) lower expression of AFP mRNA in DEN/AAF rats treated with ZER than those untreated. From the TUNEL assay, the numbers of apoptotic cells were significantly (P<O.05) higher in DEN/AAF rats treated with ZER than those untreated. Antitumor activities of ZER were further confirmed by transmission electron microscopy, which showed distinctive morphological changes corresponding to typical apoptosis. Zerumbone treatment had also increased Bax and decreased Bcl-2 proteins expression with a concurrent increase in Bax/Bcl-Z ratio with respect to DEN/AAF rats. which again suggested increased apoptosis, This was supported by similar changes in levels of Bax and Bcl-2 mRNAs. The in vivo study suggests that ZER reduces oxidative stress, inhibits proliferation, induces mitochondria-regulated apoptosis, thus minimising DEN/AAFinduced carcinogenesis in rat livers. The MTT assay suggested that ZER (IC50=3.9 ± 0.64 ug/ml.) was cytotoxic to the liver cancer cell while harmless to the normal Jiver cells. This shows that the mode of death in ZER-trcated liver cancer cells was apoptosis, as indicated by the up-regulation of caspase-J in these cells. The ZER-triggered apoptosis in liver cancer cells was preceded by redox change that generated of reactive oxygen species. Therefore, ZER has great potential in the treatment of hepatocellular carcinomas.